Theoretical and computational aspects of electronic transport at the nanoscale - Rocha, Alexandre Reily (Trinity College (Dublin, Ireland). School of Physics, 2007)
The problem of electronic transport in systems comprising only a handful of atoms is one of the most exciting branches of nanoscience. The aim of this work is to address the issue of non-equilibrium transport at the nanoscale. At first, we lay down the theoretical framework based on Keldysh's non-equilibrium Green function formalism. We show how this formalism relates to the Landauer-Buttiker formalism for the linear regime and how the current through a nanoscopic system can be related to a rate equation for which a steady state solution can be found. This formalism can be applied with different choices of Hamiltonian. In this work we choose to work with the Hamiltonian obtained from density functional theory which provides an accurate description of the electronic structure of nanoscopic systems. The combination of NEGFs and D FT results in Smeagol, a state-of-the-art tool for calculating materials-specific electronic transport properties of molecular devices as well as interfaces and junctions.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin